2016
DOI: 10.1159/000442342
|View full text |Cite
|
Sign up to set email alerts
|

<smlcap>L</smlcap>-Carnitine for Treatment of Pegasparaginase-Induced Hepatotoxicity

Abstract: Introduction: Similar to pediatric regimens, multiple doses of L-asparaginase (PEG-Asp) are being increasingly used in adults with newly diagnosed acute lymphoblastic leukemia (ALL) with promising results. One of the most common side effects of the drug in adults is high-grade hyperbilirubinemia and transaminitis. Despite being almost always reversible and may not recur, clinicians may still be reluctant to continue with PEG-Asp in patients with liver toxicity, losing the benefit from multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 10 publications
0
39
1
Order By: Relevance
“…Although toxicities associated with pegaspargase may be more significant during induction chemotherapy, it is prudent to be mindful of these toxicities, which occur more frequently in adult patients . Avoiding concomitant hepatotoxic medications and using ursodiol, vitamin B, and levocarnitine in patients who develop or are at higher risk of hepatotoxicity may be considered …”
Section: Anticipated Scenarios Prone To Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although toxicities associated with pegaspargase may be more significant during induction chemotherapy, it is prudent to be mindful of these toxicities, which occur more frequently in adult patients . Avoiding concomitant hepatotoxic medications and using ursodiol, vitamin B, and levocarnitine in patients who develop or are at higher risk of hepatotoxicity may be considered …”
Section: Anticipated Scenarios Prone To Complicationsmentioning
confidence: 99%
“…Hepatotoxicity associated with pegaspargase can be severe and preclude anticipated chemotherapy. The use of vitamin B complex in combination with levocarnitine at doses of 50‐150 mg/kg/day has been shown to mitigate this toxicity and is currently being studied as a means to shorten the severity and duration of hepatotoxicity in patients receiving pegaspargase . Consensus guidelines for management of additional asparaginase‐associated toxicities should also be referenced .…”
Section: Anticipated Scenarios Prone To Complicationsmentioning
confidence: 99%
“…Whether it can be omitted as was done in 2 of the patients who attained remission remains unclear. Notably, carnitine can be used to prevent haptic toxicity in patients with fatty liver disease and it may reduce PEG-asparaginase hepatotoxicity [8]. Additionally, Erwinia asparaginase can be used if a patient has a history of allergy to PEG-asparaginase.…”
mentioning
confidence: 99%
“…However, the mechanism of L-asparaginase-associated hepatotoxicity is not clear. There are few reports on the treatment of L-asparaginase-associated hepatotoxicity [234]. An experimental study conducted by Roesmann et al [2] reported that when L-carnitine is administered in combination with L-asparaginase for steatosis, carnitine reduces the toxicity associated with L-asparaginase.…”
mentioning
confidence: 99%
“…An experimental study conducted by Roesmann et al [2] reported that when L-carnitine is administered in combination with L-asparaginase for steatosis, carnitine reduces the toxicity associated with L-asparaginase. Alshiekh-Nasany and Douer [3] reported that polyethylene glycol (PEG)-asparaginase related high-grade liver toxicity in adult patients could be rapidly and permanently reversed using the amino acid derivate L-carnitine. Al-Nawalki et al [4] reported that histopathological macrovesicular steatosis was detected in 3 adult patients who developed L-asparaginase toxicity, and that the hepatotoxicity resolved after administration of carnitine and a vitamin B complex.…”
mentioning
confidence: 99%